Legal Aspects of Using Deepfake in Political Campaigns: A Threat to Democracy? - Lestari, Mugi; Ibrahim, Riza (Communication in Research and Publications (CRP), 2025)
This study examines the legal aspects of the use of deepfake technology in political campaigns and its implications for the integrity of democracy. Through a qualitative approach with normative legal analysis methods, this study maps regulations related to deepfake in various countries, analyzes case studies of the use of deepfake in political campaigns, and evaluates the effectiveness of regulations in Indonesia. The results show that regulations on deepfake in political campaigns vary significantly between countries, with some countries such as the United States (at the state level) and the European Union having implemented specific regulations, while Indonesia still relies on the Electronic Information and Transactions Law (UU ITE) which does not specifically regulate deepfake. Case study analysis reveals the use of deepfake for positive purposes such as translating political speeches (India) and negative purposes such as spreading disinformation (United States, Russia, Philippines). The main challenges to regulation in Indonesia include the lack of public awareness, limited detection technology, the speed of information dissemination on social media, and the absence of specific sanctions for the misuse of deepfake in a political context. Based on these findings, this study recommends the establishment of specific regulations related to deepfake, strengthening multi-party collaboration in developing detection systems, increasing public education through digital literacy campaigns, and implementing strict law enforcement with specific sanctions. A synergy between comprehensive regulation, advanced detection technology, and high public awareness is needed to mitigate the negative impact of deepfakes on democratic integrity and ensure that this technology is used ethically in political communication.